Prevalence of elderly patients who refuse to get discharge from coronary intensive care unit in a tertiary care hospital of North India: a pilot study - Singla, Sanjeev Kumar; Singla, Ankush; Panditrao, Mridul; Bansal, Ishan; Singh, Rakendra (International Journal of Research in Medical Sciences, 2019)
Background: The elderly population ≥60 years is increasing as the life span is increasing. So is the number of elderly patients who are refusing to get discharge from the hospital is also increasing. Authors are conducting this study in the elderly population who want to stay against medical advice.The aim to find the prevalence of elderly patients who refuse to get discharge from Coronary Care Unit (CCU) in a Tertiary care hospital of North India Methods: A retrospective, observational study conducted in patients of age ≥60 years admitted to the coronary intensive care unit of a tertiary health care centre who refused discharge from the unit, were included in the study. Results: Of the 575 patients 44(7.65%) were willing to stay against medical advice. Of these 24(54.5%) were males and 20(45.5%) females. 6(13.6%) patients were terminally ill suffering from malignancies. Among all the patients who were willing to stay against medical advice, 8(18.2%) were covered by some health insurance scheme of either State or Central Government. 3(6.8%) patients were discharged after 24 hours, 22(50%) patients after 48 hours, 14(31.9%) patients after 72 hours and 5(11.3%) patients after 96 hours of advising discharge from hospital. Conclusions: As the intensive care beds at tertiary healthcare level are limited, the treatment of other salvageable sick patients who need the intensive care is affected by the unnecessary stay in hospital. Apart from the worsened nurse to patient ratio this increases the cost of treatment. This is need of hour to provide safe environment for the elderly outside the hospital settings and increase resources to provide better homecare.